2002
DOI: 10.1002/ca.10058
|View full text |Cite
|
Sign up to set email alerts
|

Anterior coracoscapular ligament and suprascapular nerve entrapment

Abstract: A reduction in the height of the suprascapular foramen may predispose to entrapment of the suprascapular nerve. In this study, 16 of 27 cadavers (60%) demonstrated a heretofore unreported ligament located on the anterior aspect of the suprascapular foramen. In 11 of the 27 cadavers (41%), the ligament was observed bilaterally. The ligament decreased the foraminal height from the normative value of 5.6 +/- 0.4 to 2.3 +/- 0.4 mm (mean +/- SEM). Because this ligament, for which we propose the term anterior coraco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 12 publications
6
58
1
Order By: Relevance
“…An additional anterior coracoscapular ligament which is arranged either parallel or oblique to STSL in the suprascapular notch was first described by Avery et al [15].The ossification of only this anterior coracoscapular ligament without involving the STSL results in the coexistence of notch and foramen thus increasing the possibility of nerve entrapment in the foramen [16]. This type of presentation does not find a place in Rengachary's classification.…”
Section: Resultsmentioning
confidence: 99%
“…An additional anterior coracoscapular ligament which is arranged either parallel or oblique to STSL in the suprascapular notch was first described by Avery et al [15].The ossification of only this anterior coracoscapular ligament without involving the STSL results in the coexistence of notch and foramen thus increasing the possibility of nerve entrapment in the foramen [16]. This type of presentation does not find a place in Rengachary's classification.…”
Section: Resultsmentioning
confidence: 99%
“…Avery et al [2] discovered that the anterior coracoscapular ligament (ACSL) might have been supposed as a new possible mechanism for the formation of this anatomical variation. Polguj et al [38] observed the presence of the ACSL as 60% of 54 dissected shoulders, and they found that the SN always has been passing under the ACSL; therefore, it has been in close contact to the bony floor of the SSN [38].…”
Section: Discussionmentioning
confidence: 99%
“…The probable mechanism of formation in cases with parallel course of both bony bridges, as it is in our case, is that either the upper bony bridge was created by ossification of the single bundle superior transverse scapular ligament and the lower one was created by the osseous transformation of the anterior coracoscapular ligament, or both bridges were formed as a result of the ossification of the superior and inferior bands of the trifid superior transverse scapular ligament. As the trifid superior transverse scapular ligament was reported on rare occasions in the literature [25,35], whereas the frequency of anterior coracoscapular ligament varied up to 60% [4], the formation of the lower bony bridge by ossification of the anterior coracoscapular ligament seems to be more probable explanation.…”
Section: Discussionmentioning
confidence: 99%
“…These cases are associated with suprascapular entrapment neuropathy [5,8,10,24]. Avery et al [4] and Polguj et al [26] considered the ossification of anterior coracoscapular ligament, which causes a reduction in the height of the suprascapular foramen, also as a possible aetiologic factor in suprascapular nerve entrapment. According to Ofusori et al [21], the complete absence of the SSN could be considered as a possible cause of suprascapular nerve entrapment as well.…”
Section: Introductionmentioning
confidence: 99%